Soil biota and ecosystem development in post mining sites - Frouz, Jan (Taylor & Francis, 2013)
"Mining supplies numerous raw minerals that are essential for economic development. In many cases, however, mineral extraction causes severe destruction of the environment. Large areas can be literally erased by excavation and dumping of overburden. In addition, mining and postprocessing of raw materials may accelerate weathering processes and chemically alter the environment through, for example, acidification or pollution by heavy metals. Environmental damage brings the necessity for ecosystem reconstruction in affected areas. Numerous approaches to land reclamation have been developed. Natural processes collectively referred to as ecological succession, however, bring about gradual ecosystem development without the assistance of man. These processes may be relatively slow, particularly in their early stages, but there are many examples of how they have led to the development of functional ecosystems in the longterm, typically after several decades. In this book, we pay attention to the study of these successional processes. Firstly, only comparisons between the results of reclamation technologies and those of natural succession at unreclaimed sites of the same age can provide us with real information about the added value of reclamation. Secondly, a better understanding of natural succession processes may inspire numerous future improvements to restoration technologies. Finally, postmining sites represent an excellent model for studying succession processes and may substantially improve our knowledge about these ecological phenomena"--Provided by publisher.
Keywords: Soil ecology.; Abandoned mined lands reclamation.; Ecological succession.; Soil formation.; Soil restoration.; Biotic communities.; Soil biology.; elektronické knihy; electronic books